Structure and dynamics of highly turbulent premixed combustion. (July 2021) - Steinberg, Adam M.; Hamlington, Peter E.; Zhao, Xinyu
Abstract: Turbulent premixed combustion involves simultaneous and mutually interacting fluid, chemical, and transport phenomena spanning a wide range of spatial and temporal scales. Many practical combustion devices – such as gas turbine combustors, afterburners, and ramjets – operate with turbulent flows that contain length and time scales smaller than those associated with premixed flame propagation. This paper reviews current knowledge and understanding of premixed flames at such "highly turbulent" conditions, including the effects of turbulence on the flame and of the flame on turbulence. At these conditions, turbulent fluid motions can have a leading-order effect on the flame thermochemical structure, scalar gradients, and the resultant scalar dynamics. At the same time, the turbulent flow itself is affected by heat release from the flame, resulting in differences compared to classical non-reacting turbulence and to turbulence in flames at lower intensities. We therefore aim to address the following overarching questions: (a) What are highly turbulent premixed flames, how do we characterize them, and what are some of their macroscale behaviors? (b) How are the flame thermochemical states, scalar gradients, diffusion, and other aspects of the flame structure affected by intense turbulence? (c) How are the structure and dynamics of the turbulence affected by the presence of the flame in terms of fluxes, spectra, kinetic energy, and other relevant quantities? We also provide a summary of critical knowledge gaps and an outlook for future research directions.